Analisis Strategi Pemasaran Daring dalam Meningkatkan Penjualan UMKM Jok Boncengan Anak di Dusun Bancar - Hanafiyah, Ervina (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
Marketing strategy is one of the main keys to business success, including online marketing strategy. In the era of digitalization like today, online marketing is one of the golden opportunities for business actors, one of which is a child bike seat manufacturer in Bancar Hamlet. The purpose of this study is to find out how the online marketing strategy is implemented by this UMKM and how it affects the sales rate of child bike seats. Researchers used Basu Swastha and Irawan's theory. The research method is a qualitative method for descriptive analysis of the results of interviews and observations. The location of this research is in Bancar, Singkalanyar, Prambon, Nganjuk, RT 018 RW 008. Based on the objectives of this study, the results and discussion are as follows: online sales are carried out on Shopee and Lazada. The online marketing strategy applied includes promotions in the form of discounts, cooperation with distributors, and paid advertising on Shopee. Besides that, the owner also has strategies such as the marketing mix strategy and SWOT analysis strategy, which are used as references to maintain products in the era of intense competition. The effect of the online marketing strategy implemented by the child bike seat manufacturer apparently has a positive and significant impact on the sale of its products. This can be seen from the sales data submitted by the author. In conclusion, this marketing strategy has a good impact on the sales improvement of the UMKM child bike seat.
Keywords: Online Marketing; Marketing Strategy; Sales Rate